2012
DOI: 10.1007/s00125-012-2780-1
|View full text |Cite
|
Sign up to set email alerts
|

HLA-dependent autoantibodies against post-translationally modified collagen type II in type 1 diabetes mellitus

Abstract: Aims/hypothesis In this study the involvement of oxidative stress in type 1 diabetes mellitus autoimmunity and the possible association with rheumatoid arthritis (RA) was investigated. We tested the hypothesis that oxidative stress induced by chronic hyperglycaemia triggers post-translational modifications and thus the formation of neo-antigens in type 1 diabetes, similar to the ones found in RA. Methods Collagen type II (CII), a known autoantigen in RA, was treated with ribose and various reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Interestingly, we did not observe increased reactivity to glycated insulin in our study. This is in contrast to the increased autoreactivity to glycated collagen type II that we have previously observed [7,13]. Although this might imply that imbalance of the redox state and hence ROS production is more In this study, we developed an ELISA for detecting autoreactivity to oxPTM-INS.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Interestingly, we did not observe increased reactivity to glycated insulin in our study. This is in contrast to the increased autoreactivity to glycated collagen type II that we have previously observed [7,13]. Although this might imply that imbalance of the redox state and hence ROS production is more In this study, we developed an ELISA for detecting autoreactivity to oxPTM-INS.…”
Section: Discussionmentioning
confidence: 65%
“…It is interesting to note that one of the observed modifications involving chlorination of Tyr16 of chain B (Tyr B16) is within the region 9-23 of chain B (B:9-23), a known dominant epitope in autoimmune diabetes [21], with Tyr16 being crucial in immunoreactivity. Substitution of Tyr in position 16 to Ala (Tyr B16:Ala) has been shown to abrogate T cell reactivity [22,23], and administration of a modified B:9-23 (Tyr B16:Ala) peptide has been reported to suppress expression of IAA and prevent diabetes in the NOD mouse [24]; conversely, it is possible that Tyr16 modification by HOCl oxPTM by ROS appears to play a key role in the pathogenesis of several human autoimmune diseases [13,[25][26][27]. This is of particular relevance to type 1 diabetes, where islet inflammation and the ensuing hyperglycaemia are substantial sources of ROS production [2,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients carrying the HLA-DRB1*04 allele showed the highest risk for autoimmunity against modified collagen, while carrying a DRB1*0301 allele was protective. Autoimmunity to native collagen type II was not associated with any DRB1 alleles [44]. This study therefore highlights that, in addition to the importance of formation of PTMs for creating neo-epitopes, specific HLA genotypes can be important for the presentation of these neoepitopes to the immune system.…”
Section: Introductionmentioning
confidence: 74%
“…Recently, we [84] demonstrated that oxidative modification significantly increased the antigenicity of CII in type-I diabetes patients that carried the HLA-DRB1*4 allele associated with increased RA prevalence, but to a lesser extent in patients without the RA associated HLA-DRB1*4. These data indicate a role of oxidative PTMs in autoimmunity in type-I diabetes patients.…”
Section: Modification Of Proteins By Free Radicals and Other Reactivementioning
confidence: 99%